2022
DOI: 10.1002/suco.202200142
|View full text |Cite
|
Sign up to set email alerts
|

Basalt fiber reinforced foam concrete with marble waste and calcium aluminate cement

Abstract: As a typical cellular lightweight material, foam concrete is produced by mixing cement, water, aggregate and a suitable foaming agent and has a density usually below 1600 kg/m3. The large number of air spaces present in foam concrete ensures that the concrete has advantages such as lightweight, high fluidity during pouring, excellent thermal and sound insulation, superior fire resistance, and outstanding energy absorption capacity. Its high porosity and the connectivity of the pores, which can allow the entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Subsequently, when these stones are prepared for use by processing, sawing, and shaping them, a huge amount of powder waste is produced, which causes a global environmental problem. Therefore, the recycling of waste marble powder (WMP) in the building sector for the manufacture of sustainable concrete as a replacement for cement has been the subject of several studies in the past decade [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. This trend of studies has grown to minimize final construction costs, since WMP is very cheap and could be available for free, as well as to reduce global pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, when these stones are prepared for use by processing, sawing, and shaping them, a huge amount of powder waste is produced, which causes a global environmental problem. Therefore, the recycling of waste marble powder (WMP) in the building sector for the manufacture of sustainable concrete as a replacement for cement has been the subject of several studies in the past decade [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. This trend of studies has grown to minimize final construction costs, since WMP is very cheap and could be available for free, as well as to reduce global pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Remaining undegraded in nature for a long time since it has a long half-life, heavy metals that accumulate in bodies of organisms and can be toxic or carcinogenic even when at low concentrations are considered as one of the most dangerous environmental pollution factors [57][58][59][60]. For this reason, use of waste materials (especially heavy metals), many of which are important environmental pollutants, as a concrete additive is very important since it decreases the cost of concrete and it contributes to the reduction of environmental pollution by eliminating the environmental pollutants through recycling [61][62][63][64]. For this reason, many studies examining the use of various waste materials as concrete additives were carried out in recent years [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, on exposure to a solution of 5% hydrochloric acid, the mass loss of OPC foam concrete increased with decreased density, due to increased porosity leading an increase in the acid-exposed contact area and acid diffusion rate. The mass loss decreased with increasing basalt fiber content, due to the higher acid erosion resistance of basalt fiber [90]. Rokiah et al claimed that foam concrete in which 30% of its weight was replaced with processed spent bleaching earth experienced a lower mass loss in pH 2 hydrochloric acid solution than pure OPC foam concrete, indicating enhanced acid erosion resistance.…”
Section: Resistance To Acid Environmentmentioning
confidence: 99%